CLASSIFICATION OF ANTONYMS ("Conference on Universal Science Research 2023", 2023)
This article provides a comprehensive examination of the classification of antonyms, delving into the nuanced structures that underpin these linguistic opposites. The author navigates through various types of antonyms, including gradable, complementary, relational, converses, auto-antonyms, reversives, and relational opposites. The article begins with a clear introduction, emphasizing the pivotal role of antonyms in language and the need for a systematic classification. It then meticulously explores each antonym type, offering lucid examples to illustrate their unique characteristics.